2001
DOI: 10.1021/ol0160304
|View full text |Cite
|
Sign up to set email alerts
|

Formal Synthesis of Uvaricin via Palladium-Mediated Double Cyclization

Abstract: [see reaction]. A novel palladium-mediated, ligand-controlled double cyclization is reported. The C2-symmetric diene produced was desymmetrized via Sharpless asymmetric dihydroxylation and was further transformed into a known intermediate in the synthesis of uvaricin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 48 publications
(15 citation statements)
references
References 16 publications
0
15
0
Order By: Relevance
“…265 The resulting diene 614 was further transformed into a known intermediate 615 for the synthesis of uvaricin. They demonstrated that palladium(0)-catalyzed desymmetrization of the C 2 diol 616 with Trost's ligand 607 afforded the tetrahydrofuran 617 diastereoselectively (Scheme 188).…”
Section: Stereo-and Enantioselective Allylationmentioning
confidence: 99%
“…265 The resulting diene 614 was further transformed into a known intermediate 615 for the synthesis of uvaricin. They demonstrated that palladium(0)-catalyzed desymmetrization of the C 2 diol 616 with Trost's ligand 607 afforded the tetrahydrofuran 617 diastereoselectively (Scheme 188).…”
Section: Stereo-and Enantioselective Allylationmentioning
confidence: 99%
“…For example, in Hoye's synthesis of the annonaceous acetogenin (+)-parviflorin, bis(epoxide) 5 was desymmetrized via reaction with a limited quantity of a lithium acetylide, giving alcohol 6 (29%) along with recovered 5 (53%). 10 Two syntheses from the Burke group utilized this approach, including a related annonaceous acetogenin, uvaricin (not shown), using a dihydroxylation, 11 and the C(37)-C(54) halichondrin B subunit, using an olefination/hydroboration/oxidation sequence to convert bis(lactone) 7 to desymmetrized primary alcohol 8 in 40% yield. 12 In a remarkably brief route to (+)-roxaticin that showcases this approach, the Krische group desymmetrized diol 9 via mono-selenide 10 formation in 50% yield.…”
Section: Introductionmentioning
confidence: 99%
“…In 2001, Burke’s group reported the synthesis of a known intermediate 232 in the synthesis of uvaricin ( 225 ) ( Scheme 31 ) [ 86 ]. A chiral DPPBA ligand controlled double cyclization of 230 allowed the selective formation of a single diastereomer 231 in one step, thus providing general access to annonaceous acetogenins containing trans / threo / trans or cis / threo / cis bis-THF core structures.…”
Section: Reviewmentioning
confidence: 99%